CYA : securing Exchange Server 2003 and Outlook Web Access : cover your a** by getting it right the first time - Walther, Henrik (CYA., 2004)
CYA comes out and says what most IT Professionals are already thinking, and on that point alone it will quickly capture the attention of its target audience.